Relación entre el nivel de conocimiento de higiene oral y la necesidad de tratamiento periodontal en gestantes que acudieron al Centro de Salud Jerusalén, La Esperanza - Trujillo, en los meses de noviembre a marzo del 2011 - Ferrer Arroyo, Evert (2012)
This research made from November to March, 2011, determined the relationship between the oral hygiene knowledge level and the need of periodontal treatment in pregnant women that went to Jerusalem Health Center from La Esperanza-Trujillo. This was a descriptive, transversal and observational research. The sample was made up of 115 pregnant women of the total population under investigation. The oral hygiene knowledge level of the pregnant women was regular, with 71, 30%; bad with 24, 35% and good with 4, 35%. The need of periodontal treatment of the pregnant women was: instruction of oral hygiene with 69, 57%, scaling, 17, 39% and do not need periodontal treatment, 13, 04%. The results show than there is no significant relationship (P>0,05) between the oral hygiene knowledge level and the need of periodontal treatment of pregnant women.